Assessment of Magnitude and Factors Associated with Birth Preparedness and Complication Readiness among Pregnant Women Attending Antenatal Care Services at Public Health Facilities In Debrebirhan Town, Amhara, Ethiopia, 2015 (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: birth preparedness; complication readiness; debrebirhan; ethiopia